Serum D-dimer is not predictive of placenta-mediated complications in pregnancy at high risk: The multicentric prospective cohort AngioPred study - Hovine, Agathe; Chauleur, Céline; Gauld, Christophe; Rancon, Florence; Gris, Jean-Christophe; Tardy, Brigitte; Giraud, Antoine; Raia-Barjat, Tiphaine (Frontiers in Cell and Developmental Biology, 2023)
Background: The theory that D-dimer level might has a predictive or diagnostic role in preeclampsia needs to be explored. Aim of the study was to evaluate the association between serum D-dimer level and the occurrence of placenta-mediated complications (PMC) in a pregnant population at high risk. Methods: A prospective multicenter cohort study including 200 pregnant women was conducted. Results: Serum D-dimer increases throughout pregnancy, with the highest levels at the end of gestation. Serum D-dimer level was similar for women with PMC and with no complication. Serum D-dimer level was not different in women with preeclampsia versus uncomplicated women. Serum D-dimer level was not different in women with early or late preeclampsia versus uncomplicated women. Conclusion: This result suggests that serum D-dimer level was not predictive of the PMC occurrence. This corroborates the fact that the origin of PMC based more on immunity than in hemostasis.